Sleep and Association With Cardiovascular Risk Among Midwestern US Firefighters - Romero Cabrera, Juan Luis; Sotos-Prieto, Mercedes; García Ríos, Antonio; Moffatt, Steven; Christophi, Costas A.; Pérez-Martínez, Pablo; Kales, Stefanos N. (Frontiers in Endocrinology, 2021)
Introduction: Cardiovascular disease is the leading cause of on-duty fatalities among U.S. firefighters. Research has demonstrated that many modifiable risk factors are contributors to the high prevalence of cardiometabolic risk factors. The current study aimed to assess whether sleep is associated with cardiometabolic risk factors among Indianapolis firefighters. The findings could support improving sleep hygiene in this population. Material and methods: This cross-sectional study was conducted from the baseline data of eligible firefighters enrolled in “Feeding America’s Bravest”, a Mediterranean diet lifestyle intervention within the Indiana Fire Departments. Participants’ sleep quality was categorized as “good” (≤ 8 points) or “bad” (>8 points) by a sleep quality questionnaire based on some questions from Pittsburgh Sleep Quality Index. In addition, firefighters’ sleep duration was stratified based on the number of hours slept per night (≤6 as “short sleep” or >6 hours as normal). Linear and logistic regression models were used to examine the association of sleep with cardiometabolic risk factors. Results: A total of 258 firefighters were included. Bad sleepers had higher weight, greater waist circumference, higher body mass index (BMI), and increased body fat (all p<0.01) compared to good sleepers. Similarly, participants with short sleep duration were heavier (p<0.02), had greater BMI (p<0.02) and increased body fat (p<0.04) compared with participants with normal sleep duration. Both bad and short sleepers had a higher prevalence of hypertension and obesity (p <0.05). Conclusions: Our study supports that both sleep quality and quantity are associated with cardiometabolic risk among firefighters.